Joseph Sewall papers - Sewall, Joseph, 1795-1851.; Sewall, Frederick Dummer, 1826-1907.
General business correspondence, including correspondence with the U.S. Dept. of the Treasury, account books, printed documents, receipts, abstracts, and business files relating to Sewall's position as collector of customs, 1832-1842. Includes correspondence, certificates, and military papers of Frederick Dummer Sewall, who served as a U.S. Army officer during the Civil War and special agent in the office of the Commissioner of Internal Revenue. Joseph Sewall's correspondents include John Campbell, U.S. Treasurer, and Levi Woodbury, U.S. Secretary of the Treasury.
Adjutant general of Maine and collector of customs for the District of Bath.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Campbell, John, -- 1789-1866 -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; United States. -- Office of Commissioner of Internal Revenue; United States. -- Department of the Treasury -- Correspondence; Customs administration -- Maine; Bath (Me.) -- History; United States -- History -- Civil War, 1861-1865.; Adjutants general; Customs agents